Literature 1991-1995 - Allen, Sture [ed.] (Singapore World Scientific, 1997)
Equally important to our understanding of history and humanity are the great works of literature. The Nobel Prize for literature recognizes modern classics and the efforts of authors to bridge gaps between different cultures, time-periods and styles.(1991) N GORDIMER - who through her magnificent epic writing has - in the words of Alfred Nobel - been of very great benefit to humanity; (1992) D WALCOTT - for a poetic oeuvre of great luminosity, sustained by a historical vision, the outcome of a multicultural commitment; (1993) T MORRISON - who in novels characterized by visionary force and poetic import, gives life to an essential aspect of American reality; (1994) K OE - who with poetic force creates an imagined world, where life and myth condense to form a disconcerting picture of the human predicament today; (1995) S HEANEY - for works of lyrical beauty and ethical depth, which exalt everyday miracles and the living past.
Keywords: Literature, Modern -- 20th century; Nobel prizes